2021
DOI: 10.1038/s41598-021-85182-w
|View full text |Cite
|
Sign up to set email alerts
|

Sanger sequencing is no longer always necessary based on a single-center validation of 1109 NGS variants in 825 clinical exomes

Abstract: Despite the improved accuracy of next-generation sequencing (NGS), it is widely accepted that variants need to be validated using Sanger sequencing before reporting. Validation of all NGS variants considerably increases the turnaround time and costs of clinical diagnosis. We comprehensively assessed this need in 1109 variants from 825 clinical exomes, the largest sample set to date assessed using Illumina chemistry reported. With a concordance of 100%, we conclude that Sanger sequencing can be very useful as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…By convention, NGS results necessitate validation by Sanger sequencing as the reference standard. However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [38,39]. Arteche-Lopez et al, reported their validation study of 1109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By convention, NGS results necessitate validation by Sanger sequencing as the reference standard. However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [38,39]. Arteche-Lopez et al, reported their validation study of 1109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [38,39]. Arteche-Lopez et al, reported their validation study of 1109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [38]. Only three discrepancies were found, and all false negative results arose from Sanger sequencing [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By convention, NGS results necessitate validation by Sanger sequencing as the reference standard. However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [25,26]. Arteche-Lopez et al, reported their validation study of 1,109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [25,26]. Arteche-Lopez et al, reported their validation study of 1,109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [25]. Only 3 discrepancies were found, and all false negative results arose from Sanger sequencing [25].…”
Section: Discussionmentioning
confidence: 99%